HRM practices and organizational performance: Organizational climate as a moderator: A proposed conceptual framework - Abdul Rahman, Azura; AB Hamid, Kamal (2017)
There is a growing body of literature that recognises the importance of human resource management practices (HRM practices) in enhancing the organizational performance.The purpose of this study is to propose a framework of key human resource (HRM) practices that can contribute to the performance of the organization.The nature of what is the best HRM practice are remains unclear.Based on previous research, some studies have reported mixed findings. Therefore, this paper proposed organizational climate as a potential moderator on the relationship between HRM practices and organizational performance.